PIP2;1 aquaporin gene expression in maize hybrids different for drought tolerance to water deficit - Ovrutska, I.I.; Kordyum, E.L. (Доповіді НАН України, 2019)
At the mRNA level, different PIP2;1 aquaporin gene expressions in roots of drought-tolerant and drought-sensitive maize genotypes with sufficient substrate moisture, as well as their distinct responses towards water deficit, are shown. An analysis of the obtained data allow us to consider PIP2;1 expression as a possible molecular marker in maize breeding for drought tolerance.